2007
DOI: 10.1111/j.1538-7836.2007.02300.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to air pollution on blood coagulation

Abstract: Summary. Background: Consistent evidence has indicated that air pollution increases the risk of cardiovascular diseases. The underlying mechanisms linking air pollutants to increased cardiovascular risk are unclear. Objectives: We investigated the association between the pollution levels and changes in such global coagulation tests as the prothrombin time (PT) and the activated partial thromboplastin time (APTT) in 1218 normal subjects from the Lombardia Region, Italy. Plasma fibrinogen and naturally occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
131
3
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(151 citation statements)
references
References 46 publications
(74 reference statements)
14
131
3
3
Order By: Relevance
“…Global coagulation tests (prothrombin time and activated partial thromboplastin time), as well as plasma fibrinogen levels and naturally occurring anticoagulant proteins (antithrombin, protein C and protein S), were evaluated in 1218 healthy individuals and related to the degree of air pollution (PM 10 , CO, NO 2 , SO 2 and O 3 ) in the hours and days before blood sampling. A significant correlation was found between mild shortening of the prothrombin time and the degree of air pollution, both at the time of sampling or in the 30 days prior to sampling [64]. Short-term exposure to PM 10 was also associated with increased homocysteine levels in smokers, but not in non-smokers [65].…”
Section: Potential Mechanismsmentioning
confidence: 64%
See 1 more Smart Citation
“…Global coagulation tests (prothrombin time and activated partial thromboplastin time), as well as plasma fibrinogen levels and naturally occurring anticoagulant proteins (antithrombin, protein C and protein S), were evaluated in 1218 healthy individuals and related to the degree of air pollution (PM 10 , CO, NO 2 , SO 2 and O 3 ) in the hours and days before blood sampling. A significant correlation was found between mild shortening of the prothrombin time and the degree of air pollution, both at the time of sampling or in the 30 days prior to sampling [64]. Short-term exposure to PM 10 was also associated with increased homocysteine levels in smokers, but not in non-smokers [65].…”
Section: Potential Mechanismsmentioning
confidence: 64%
“…The effects of exposure to air pollution on blood coagulation were investigated in a study conducted in the region of Lombardy in the north of Italy [64]. Global coagulation tests (prothrombin time and activated partial thromboplastin time), as well as plasma fibrinogen levels and naturally occurring anticoagulant proteins (antithrombin, protein C and protein S), were evaluated in 1218 healthy individuals and related to the degree of air pollution (PM 10 , CO, NO 2 , SO 2 and O 3 ) in the hours and days before blood sampling.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Moreover coagulation factors such as FVII and fibrinogen, which are part of the acute phase responses mediated by cytokines released during inflammatory reactions, increase after short-term exposure to particles (Schwartz J et al, 2001;Ruckerl R et al, 2014). As already mentioned before, Baccarelli et al, (Baccarelli et al, 2007) founded that a shorter prothrombin time (PT) was associated with higher concentrations of ambient PM 10 , CO and NO 2 . This suggests that air pollution determines hypercoagulability and contributes to the increase in cardiovascular effects observed after exposure to air pollution.…”
Section: Air Pollution Blood Pressure and Coagulationmentioning
confidence: 88%
“…Hypercoagulability and heightened platelet activation also occur through pulmonary and systemic inflammation and generate a cytokine storm, a mechanism that facilitates atherogenesis (Vermylen j et al, 2007). Baccarelli et al, demonstrated that a global coagulation test like prothrombin time (PT) becomes shorter during exposure to high ambient air concentrations of PM10 (Baccarelli A et al, 2007). This result was confirmed by Bonzini et al, who used for the first time a global functional assay of coagulability (the thrombin generation test) and demonstrated heightened thrombin formation in steel workers, who were exposed to high levels of particulate matter (Bonzini M et al, 2010).…”
Section: Air Pollution and Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…[1][2][3][4] Among the mechanistic pathway that mediates such effects, 4,5 elevated plasma levels of coagulation proteins such as factor VIII, von Willebrand factor, and fibrinogen, as well as shortened prothrombin time, have been associated with the exposure. [5][6][7][8] Recently, an association between particulate air pollution and an increased risk of deep vein thrombosis (DVT) was reported by some of us. 9 Determinants of arterial and venous thrombosis are in part different, as hypercoagulability due to a series of heritable or acquired risk factors, including the gain-of-function mutations in coagulation factor V (factor V Leiden) and prothrombin (prothrombin G20210A), deficiencies of the natural anticoagulant proteins antithrombin, protein C and protein S, and use of oral contraceptive or hormone replacement therapy, [10][11][12] is much more associated with venous than arterial thrombosis.…”
mentioning
confidence: 99%